Recalling Hindu-Javanese Voices in Bali: Anthropological Media Praxis between the Visible and the Invisible - Nozawa, Akiko (The Indonesian Journal of Social Studies, 2024)
This paper argues the potential of filmmaking to encompass “visible/tangible” and “invisible/intangible” cultural heritages, invoking W.J. Ong’s theory of “Orality and Literacy.” To exemplify the impact of media from a historical perspective, the paper takes up two cases related to the old tale of Sri Tanjung in the era of Hindu-Java in Indonesia: Prijono’s 1938 book of the lontar manuscript from Bali, and my filmmaking project in Bali, which focuses on the archaic meter in the original lontar unveiled by Prijono. The first case reveals the attribution of Prijono’s text as a product of Western literacy training that consequently marginalized the lontar's original orality as a kidung (ritual song). The second clarifies the “diversity within a norm” in reciting the meter (pupuh wuikir/adri) by Balinese successors and the similar feature of kidung videos on YouTube, representing a variety of communal oral styles shaped by ritual practices. The comparison finds that, while “text-making of Hindu-Javanese culture” by local intellectuals in the 1930s served to unite Indonesian nationalism for the future, “filming/performing kidung/kakawin” utilizing today’s digital infrastructure promotes local diversity of cultural transmission; it is reactivating the polyphonic nature of ancient manuscripts through the recursive/retrospective relationship between bodily memories and audiovisual images. Today’s bottom-up-oriented interpretive activities, through traditional performing arts, thus suggest the significance of dialogical filmmaking praxes to visualize cultural memories that were invisible until the last century, whereby technical/technological practices could explore the future vision together to transmit cultural heritage from global and local perspectives.